Behavioral Disorders in Physically Challenged Individual Sports Youth Athletes - Zaineb Sabri Hazem; Sanaa Majeed Majeed Mohammed (College of Physical Education and Sport Sciences, 2020)
The researchers aimed at identifying the effect of behavioral disorders in physically challenged individual sports athletes and the level of its effect on their life. The researchers used the descriptive method on (80) physically challenged individual sport athletes. The researchers designed a scale for behavioral disorders for physically challenged that consisted of four fields. The data was collected and treated to conclude that most athletes have mild behavioral disorders. In addition to that, the researchers concluded that athletic competitions and disability are major reasons for these disorders.